Addressing food scarcity in marginalized mountain environments: A participatory seed management initiative with women and men in Eastern Nepal - Gurung, Barun; Gurung, Pabitra (International Mountain Society (IMS) and United Nations University, 2002)
Experiences with a participatory seed improvement initiative as a strategy for combating food deficits in a remote community in eastern Nepal are outlined. On the basis of participatory methods of problem assessment, food deficits were attributed to several factors, such as limited arable land, poor soils, and lack of access to improved seeds and other agricultural services arising partly from the lowland and gender biases of national planners. Additionally, an increase in the number of households headed by women and the greater agricultural burden placed on women as a result of male out-migration have contributed to the problem of food deficits.